Local Auxin Biosynthesis Mediated by a YUCCA Flavin Monooxygenase Regulates Haustorium Development in the Parasitic Plant Phtheirospermum japonicum . Issue 8 (6th July 2016) - Ishida, Juliane K.; Wakatake, Takanori; Yoshida, Satoko; Takebayashi, Yumiko; Kasahara, Hiroyuki; Wafula, Eric; dePamphilis, Claude W.; Namba, Shigetou; Shirasu, Ken
Abstract : In the parasitic plant Phtheirospermum japonicum, the auxin biosynthesis gene YUCCA3 plays a pivotal role in the formation of haustoria, which invade host tissues and facilitate nutrient acquisition. Abstract: Parasitic plants in the Orobanchaceae cause serious agricultural problems worldwide. Parasitic plants develop a multicellular infectious organ called a haustorium after recognition of host-released signals. To understand the molecular events associated with host signal perception and haustorium development, we identified differentially regulated genes expressed during early haustorium development in the facultative parasite Phtheirospermum japonicum using a de novo assembled transcriptome and a customized microarray. Among the genes that were upregulated during early haustorium development, we identified YUC3, which encodes a functional YUCCA (YUC) flavin monooxygenase involved in auxin biosynthesis. YUC3 was specifically expressed in the epidermal cells around the host contact site at an early time point in haustorium formation. The spatio-temporal expression patterns of YUC3 coincided with those of the auxin response marker DR5, suggesting generation of auxin response maxima at the haustorium apex. Roots transformed with YUC3 knockdown constructs formed haustoria less frequently than nontransgenic roots. Moreover, ectopic expression of YUC3 at the root epidermal cells induced the formation of haustorium-like structures in transgenic P. japonicum roots. Our results suggest that expression of the auxin biosynthesis gene YUC3 at the epidermal cells near the contact site plays a pivotal role in haustorium formation in the root parasitic plant P. japonicum .